Workforce Aging in Production Systems: Modeling and Performance Evaluation. (2015) - Boenzi, F.; Mossa, G.; Mummolo, G.; Romano, V.A.
Abstract: Human factor is considered as a cost effective alternative to expensive automated solutions, as well as an easily interchangeable high flexible resource. However, for many years the influence of human behavior on production system performance has been underestimated and a lot of unrealistic assumptions have been used to simplify the human component modeling. Nowadays, population aging is acknowledged as a global trend. Among individual factors impacting on workers' performance, high attention is being paid to the age from scientific community, policy-makers and business leaders. The aim of this paper is to provide some highlights about the main scientific literature findings, regarding aging effects, in a quickly consultable and synthetic form; the elements characterizing human performance could then be included in models and ergonomic evaluation tools. In the initial part of the paper, demographic aspects and their implications on workforce composition are illustrated; successively, a state of the art of human behavior modeling is provided and main findings on age-related performance characteristics are summarized.